Cephalo pelvic disproportion in the African primigravida - Stewart, Kenneth S. (The University of Edinburgh, 1977)
Cephalopelvic disproportion, a major cause of perinatal death and morbidity in Africa, is notoriously difficult to assess both ante-natally and in labour. Recognising the limitations of medical personnel and equipment in Africa, a simple method of diagnosis and management is required. Professor Philpott with his introduction of the partogram and the "Alert Line" (1972), to African obstetrics has produced a simple screening device. This enables even a remote and inexperienced midwife to detect the primigravid patient with cephalopelvic disproportion early, and to refer her into the nearest hospital. Once in hospital, with the cervicograph across the "Action Line" (Philpott and Castle, 1972) and in the absence of complications other than dysfunctional labour and possible disproportion, active management should be instituted and an Oxytocin augmented Trial of Labour commenced. This "Trial of Oxytocin" must be closely controlled and the infant delivered at the correct time and by the correct method.